Flinovia - Flow Induced Noise and Vibration Issues and Aspects 2014
DOI: 10.1007/978-3-319-09713-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Discussion About Different Methods for Introducing the Turbulent Boundary Layer Excitation in Vibroacoustic Models

Abstract: For controlling the noise radiated from vibrating structures excited by turbulent boundary layer (TBL) it is relevant to develop numerical tools for understanding how the structure reacts to TBL excitation. Usually, the wall pressure fluctuations of the TBL are described through statistical quantities (i.e. space-frequency or wavenumber-frequency spectra) which depend on the TBL parameters. On the other hand, the vibro-acoustic models (i.e. Finite Elements, Boundary Elements, Transfer Matrix Methods, Analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…When ω increases, the convective wavenumber k c moves in the high-wavenumber region, further away from k f , and the main contributing part becomes the low-wavenumber region of the spectrum. Well above The calculation processes described in the literature generally assume that the TBL is spatially homogeneous (Maury et al, 2002;Hambric et al, 2004;Ciappi et al, 2009;Maxit et al, 2015). For practical applications, this assumption is rarely met.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When ω increases, the convective wavenumber k c moves in the high-wavenumber region, further away from k f , and the main contributing part becomes the low-wavenumber region of the spectrum. Well above The calculation processes described in the literature generally assume that the TBL is spatially homogeneous (Maury et al, 2002;Hambric et al, 2004;Ciappi et al, 2009;Maxit et al, 2015). For practical applications, this assumption is rarely met.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied different ways to achieve this coupling for spatially homogeneous TBL. Maxit et al (2015) summarized five techniques for coupling stochastic TBL and deterministic vibro-acoustic structure models:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Studies to adopt relative methods developed in the aeroacoustic fields for naval ships are being performed in a limited manner on the local elements of the structure such as square plates; however, numerical methods have limitations due to lower convective speed of turbulent flows having relatively low frequency range excitation and involving higher speed of sound propagation. 6,7 The lack of usable acoustic performance assessment methods is a cause of concern in the context of the acquirement programs of future naval ships in gaining a competitive edge at the “Noise War” considering a typical 10-year-period of the design stage and 20 years of operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the SEA method is limited to the high-frequency range where the frequency range is broad and modal density is high; thus, its limitations are more emphasized for underwater environments wherein the input force wavenumber is low and sound propagation speed is high. 6,7 In addition, it is limited to applications of local damping and input power owing to a lack of information concerning the spatial energy distributions for subsystems. 14 To overcome these limitations, among various approximating methods being developed, Belov et al 15 suggested the energy flow analysis (EFA) methods.…”
Section: Introductionmentioning
confidence: 99%